University Management: Adapting to Globalization Trends - Marisya, Fitria; Fitri Indriani, R.A. Rodia; Harapan, Edi (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
Universities need to be managed well so that they can carry out the educational process well, produce quality products, and provide satisfaction to prospective students, the community, and the world of employment. To be able to work well to meet the expectations of the community and the world employment opportunities, then higher education leaders apply Managerial Competencies, five managerial competencies of leaders in creating conducive and quality higher education institutions, namely Conceptual Competency, Interpersonal Communication Competency, Technical Competency, Time Management Competency, and Decision-Making Competence. It should be used as a reference and benchmark in higher education.